Penggunaan Pupuk Organik Cair Berfitohormon Jagung Pada Tanaman Sayuran di Pekarangan Rumah pada Kegiatan Abdimas Lingkungan - Nurhasanah Nurhasanah; A Hadian Pratama H Hamzah (Jurnal PkM Pengabdian kepada Masyarakat, 2022)
Vegetable plants planted in the yard will produce good quality vegetables if proper maintenance is carried out, one of which is given fertilizer. The recommended fertilizer is a liquid organic fertilizer with phytohormones. This study aims to see the effect of liquid organic fertilizer with phytohormones on vegetable seeds planted by residents in their yards. Residents of RT 01/RW 06 will be taught by the UT Abdimas (Community Service) Team about making and using liquid organic fertilizer with phytohormones. Details of Abdimas' activities are to provide an explanation of the meaning and benefits of phytohormones, materials around the house that can be used to make liquid organic fertilizers containing phytohormones, then the practice of making liquid organic fertilizers containing phytohormones as a base material for corn. The result of this research is that they have gained knowledge about the benefits of liquid organic fertilizer with phytohormones, they have known and are starting to become skilled in making liquid organic fertilizer with phytohormones as a basic ingredient of corn. The application of organic fertilizers with phytohormones has a good effect on vegetable crops, participants are satisfied with their harvests, the plants are more fertile and the results are large both from their vegetative growth (stems and leaves) and from their generative growth (fruit). The ability to absorb training information and implement activities is the key to the success of the program in the community.